Design and Build a Web-Based Guestbook Case Study Gresik Regency Education Office: Rancang Bangun Buku Tamu Berbasis Web Studi Kasus Dinas Pendidikan Kabupaten Gresik - Riyadi, Slamet; Astutik, Ika Ratna Indra (Universitas Muhammadiyah Sidoarjo, 2022)
This research was conducted at the Gresik Regency Education Office, namely how to design a Web-Based Guestbook and Guest Complaints Information System at the Gresik Regency Education Office. The management of guest data and guest complaints is still very conventional, so delays often occur in visiting services and in conducting guest complaint consultations. The purpose of this research is to make it easier for employees to process guest data and consult guest complaints and to make it easier for guests to register guest data and guest complaints wherever they are. This study uses the Waterfall method. The stages of the waterfall are analysis, system, coding design and testing. Methods of data collection through interviews and observation, literature study. The results of this study are to make it easier to register guests and submit/consult guest complaints and manage guest data, guest complaints.